2021
DOI: 10.1111/peps.12455
|View full text |Cite
|
Sign up to set email alerts
|

Once an entrepreneur, always an entrepreneur? Entrepreneurial identity, job characteristics, and voluntary turnover of former entrepreneurs in paid employment

Abstract: We focus on former entrepreneurs' employment in established firms. Understanding the retention of former entrepreneurs-those who were previously founders of business ventures-is important to firms hoping to reap the benefits of their entrepreneurial experience. We compare the duration of their retention to other employees without entrepreneurial experience and propose a theoretical model in which entrepreneurial identity and job characteristics play a central role. The time-dependent risk of voluntary turnover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 140 publications
(156 reference statements)
0
41
0
Order By: Relevance
“…We think that it is no longer necessary to discuss the importance of entrepreneurship research for the domains of organizational psychology and organizational behavior or vice versa. Psychological approaches have been well-received in entrepreneurship (see Gielnik et al 2021), and nearly all applied psychology journals now publish entrepreneurship research (e.g., Feng et al 2022. We provide an overview of this research and focus on two topics that have been of particular interest in the last decade: actions and the process of entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%
“…We think that it is no longer necessary to discuss the importance of entrepreneurship research for the domains of organizational psychology and organizational behavior or vice versa. Psychological approaches have been well-received in entrepreneurship (see Gielnik et al 2021), and nearly all applied psychology journals now publish entrepreneurship research (e.g., Feng et al 2022. We provide an overview of this research and focus on two topics that have been of particular interest in the last decade: actions and the process of entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%
“…The results are different from those here. This conclusion may be due to the small sample size of the study subjects from the same university and teachers ( Feng et al, 2022 ).…”
Section: Results In the Analysis Of The Influencing Factors Of Entrep...mentioning
confidence: 99%
“…Therefore, the proportion of the population and the distribution of educational background are basically consistent with the overall level of the research subjects. Feng et al (2022) found that in a study on the characteristics of entrepreneurs, most entrepreneurs were over 30 years old. The results are different from those here.…”
Section: Results In the Analysis Of The Influencing Factors Of Entrep...mentioning
confidence: 99%
“…Cox regression, a semi-parametric model (Felipe et al, 2022) is a robust technique for hazardrate analysis (Basco et al, 2020). It analyses the amount of time until an event (Warhuus, Frid and Gartner, 2021) and has been used to establish the likelihood of ventures' internationalisation and survival (Deng et al, 2022;Felipe et al, 2022;Feng, Allen and Seibert, 2021;Lee, 2021;Zettel and Garrett, 2021;Puig, Gonzalez-Loureiro and Ghauri, 2018).…”
Section: Cox Modelmentioning
confidence: 99%